PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TEMPAT MAKAN EATLAH TOKYOLK CIPETE - Chiara Praghasya Andini, - (2019)
This research is a quantitative research that aims to determine the effect of product quality, brand image, and promotion through Instagram social media on consumer purchasing decisions at Eatlah Tokyolk Cipete eating places. The population in this study were all consumers who were in the Cipete area and had made purchases at the Eatlah Tokyolk Cipete restaurant. The sample size was taken as many as 75 respondents, with a non-probability sampling method with a type of purposive sampling. Data collection is done through questionnaires. The data analysis technique used is descriptive and inferential analysis, using the Partial Least Square (PLS) tool. The results of this study indicate that (1) product quality has a significant effect on purchasing decisions with a coefficient of 0.368. (2) brand image has a significant effect on purchasing decisions with a coefficient of 0.586. (3) promotion does not have a significant effect on purchasing decisions with a coefficient of -0.051.